Transforming Activisms 2010+: Exploring Ways and Waves. Issue 3 (15th May 2013) - Biekart, Kees; Fowler, Alan; Biekart, Kees
ABSTRACT The waves of civic activism unfolding since late 2010 at a global level are striking. In major cities of the world, streets and squares have been filled with self‐organized citizens demanding attention for social and political rights. The protest images have been televised, downloaded and quickly distributed — seemingly diverse sites and types of activisms being rapidly connected and speaking to each other. Does this scale and momentum signal a tipping point in a 'globalization of disaffection'? Are we witnessing the emergence of a new age‐cohort of activists, similar to the '1968 generation'? What were the common elements, and what energy was driving the activisms of the squares and the blog spots? This Introduction to the Forum Debate section will try to position the notion of 'Activisms 2010+' in terms of its nature and relevance to current debates about citizen‐led socio‐political change. We argue that contemporary activisms constitute a distinct shift in the character of civic engagement as they surf on waves created by the increased availability and use of social media, and by a common set of rights‐based demands.